CRM Impact On SMEs Performance In Malaysian Food Manufacturing Industry - Mohamad, Siti Hajar (2015)
Customer relationship management (CRM) has been successfully implemented in the service industry as well as in large organizations. However, the application of CRM in Small and Medium Enterprises (SMEs) are still arguable. This study aims is to investigate the potential of CRM practices in enhancing the performance of SMEs. This study will focus on the management aspects of CRM. The quantitative approach was used to collect data from Malaysian food manufacturers and 2,805 companies have been targeted. There were 453 surveys were returned and 364 surveys used for Structural Equation Modelling analysis. The results indicated that technological CRM resources are not significant with the market orientation and marketing performance. Meanwhile, other constructs namely infrastructural CRM resources, key customer focus and relationship marketing are significant. The results illustrated that market orientation mediated the relationship between infrastructural CRM resources, relationship marketing and market turbulence with marketing performance. In addition market turbulence is a significant moderator toward market orientation and marketing performance, however it is not a significant moderator for market orientation and financial performance. As a result, this test proved the greater support of market performance rather than financial performance. Therefore, this study establishes the latest CRM model that has included infrastructural CRM resources and relationship marketing that is relevant for SMEs in improving their marketing performance. In a managerial point of view, this study provides a valid and applicable solution for small firms to enable companies to adopt and implement CRM in their organization. Subsequently, practical contribution shows that companies implementing CRM will have better performance in term of infrastructural CRM resources, relationship marketing and market orientation. Finally, the CRM model developed as a result of this study is easily adapted to other industries such as the textile industries, herbal industries and craft industries. Further research may be conducted to enhance the CRM model on SMEs in other countries.